David Copperfield - Dickens, Charles; Degen, Paul. (Franklin Center, Pa. : Franklin Library, 1980)
When David Copperfield's widowed mother remarries, David suffers from his stepfather's abuse. At age 8, David is sent away to a harsh school where the principal routinely beats the students. David's circumstances become even worse when he is removed from school and, at age 10, forced to labor from morning to night in a London warehouse. David then decides to take desperate action. He will run away to his great-aunt, who lives in Dover. Having never met her, David doesn't know whether she'll welcome him or reject him. With almost no money, no food, and inadequate clothing, he sets out on a journey that will change his life.
I am born -- I observe -- I have a change -- I fall into disgrace -- I am sent away from home -- I enlarge my circle of acquaintance -- My "first half" at Salem House -- My holidays, especially one happy afternoon -- I have a memorable birthday -- I become neglected, and am provided for -- I begin life on my own account, and don't like it -- Liking life on my own account no better, I form a great resolution -- Sequel of my resolution -- My aunt makes up her mind about me -- I make another beginning -- I am a new boy in more senses than one -- Somebody turns up -- Retrospect -- I look about me, and make a discovery -- Steerforth's home -- Little Em'ly -- Some old scenes, and some new people -- I corroborate Mr. Dick, and choose a profession -- My first dissipation -- Good and bad angels -- I fall into captivity -- Tommy Traddles -- Mr. Micawber's gauntlet -- I visit Steerforth at his home, again -- Loss -- Greater loss -- Beginning of a long journey -- Blissful -- My aunt astonishes me -- Depression -- Enthusiasm -- Little cold water -- Dissolution of partnership -- Wickfield and Heep -- Wanderer -- Dora's aunts -- Mischief -- Another retrospect -- Our housekeeping -- Mr. Dick fulfills my aunt's predictions -- Intelligence -- Martha -- Domestic -- I am involved in a mystery -- Mr. Peggotty's dream comes true -- Beginning of a longer journey -- I assist at an explosion -- Another retrospect -- Mr. Micawber's transactions -- Tempest -- New wound, and the old -- Emigrants -- Absence -- Return -- Agnes -- I am shown two interesting penitents -- Light shines on my way -- Visitor -- Last retrospect.
Keywords: Copperfield, David (Fictitious character); Young men -- England; Child labor; Stepfathers; England -- Social life and customs -- 19th century; Great Britain -- History -- 19th century; Autobiographical fiction